Three-dimensional collective charge excitations in electron-doped copper oxide superconductors - Hepting, M.; Chaix, L.; Huang, E. W.; Fumagalli, R.; Peng, Y. Y.; Moritz, B.; Kummer, K.; Brookes, N. B.; Lee, W. C.; Hashimoto, M.; Sarkar, T.; He, J.-F.; et al. (Nature (London), 2018)
High-temperature copper oxide superconductors consist of stacked CuO 2 planes, with electronic band structures and magnetic excitations that are primarily two-dimensional 1 , 2 , but with superconducting coherence that is three-dimensional. This dichotomy highlights the importance of out-of-plane charge dynamics, which has been found to be incoherent in the normal state 3 , 4 within the limited range of momenta accessible by optics. Here we use resonant inelastic X-ray scattering to explore the charge dynamics across all three dimensions of the Brillouin zone. Polarization analysis of recently discovered collective excitations (modes) in electron-doped copper oxides 5 – 7 reveals their charge origin, that is, without mixing with magnetic components 5 – 7 . The excitations disperse along both the in-plane and out-of-plane directions, revealing its three-dimensional nature. The periodicity of the out-of-plane dispersion corresponds to the distance between neighbouring CuO 2 planes rather than to the crystallographic c -axis lattice constant, suggesting that the interplane Coulomb interaction is responsible for the coherent out-of-plane charge dynamics. The observed properties are hallmarks of the long-sought ‘acoustic plasmon’, which is a branch of distinct charge collective modes predicted for layered systems 8 – 12 and argued to play a substantial part in mediating high-temperature superconductivity 10 – 12 . Resonant inelastic X-ray scattering on electron-doped copper oxide superconductors reveals a three-dimensional charge collective mode, which has properties suggestive of the long-sought acoustic plasmon.